Correlation of autoantibodies against BP180/BP230 in response to topical corticosteroids in patients with bullous pemphigoid - Schneiderbauer, Roland; Martinache, Stefanie; Engstner, Monika; Enk, Alexander; Hadaschik, Eva (Dermatologic therapy, 2016)
Topical steroids are effective in treating bullous pemphigoid (BP). Autoantibodies against BP180 are related to disease activity, but correlation of these autoantibodies with response to topical steroid therapy has not yet been clearly evaluated. We investigate the usefulness of close and early monitoring of autoantibodies against BP180 and BP230 for assessment of response to therapy and early detection of therapeutic failure in BP patients treated topically. In eight BP patients under treatment with topical or systemic steroid therapy we retrospectively evaluated clinical course and autoantibodies against BP180 and BP230 as well as indirect immunofluorescence titres (IIF). Data were included at diagnosis, during hospitalization and follow-ups. Autoantibodies against BP180 parallel disease activity in all topically and as well as systemically treated patients. Autoantibodies against BP230 correlated in five out of eight patients. Autoantibodies directed against BP180 and, to a lesser degree, against BP230 correlate with the clinical course of topically treated BP patients. Monitoring autoantibodies against BP180 is a useful tool to evaluate the efficacy of topical therapy in BP.
Gesehen am 20.05.2020